Numerical Simulation on Mesoscale Mechanism of Seepage in Coal Fractures by Fluid-Sloid Coupling Method. (16th March 2021) - Si, Kai; Peng, Ruidong; Zhao, Leilei; Zhao, Yan; Zhu, Yaheng; Cui, Zhendong; Zhang, Jianyong
Abstract : Trying to reveal the mechanism of gas seepage in coal is of significance to both safe mining and methane exploitation. A series of FEM numerical models were built up and studied so as to explore the mesoscale mechanism of seepage in coal fractures. The proposed mesoscale FEM model is a cube with micron fractures along three orthogonal directions. The distribution of velocity and pressure under fluid-solid coupling was obtained, and furthermore, the seepage flow flux and an equivalent permeability of the whole model were calculated. The influences of fracture width, outlet velocity, and in situ stress level on seepage were investigated. The numerical results show that nonlinear Darcy seepage occurs during low velocity zone. The permeability is increased linearly with the increasing of facture width and outlet velocity. A certain change of lateral coefficient of in situ stress also affects seepage. The permeability is increased sharply once deviating the isotropic spherical stress state, but it is no longer changed obviously after the lateral coefficient has been increased or decreased more than 20%. The mesoscale seepage mechanism in coal fractures has been preliminarily revealed by considering fluid-solid coupling effect, and the key factors influencing fluid seepage in coal fractures were demonstrated. The proposed methods and results will be helpful to the further study of seepage behaviour in coal with more complex structures.